Three-dimensional chrysanthemum-shaped CoMoO4@Ni3V / NF heterostructure catalyst and its preparation method and application
By synthesizing a three-dimensional chrysanthemum-like CoMoO4@Ni3V/NF heterostructure electrocatalyst in an alkaline medium, the problems of low energy conversion efficiency of HER and high cost of precious metal-based catalysts in the prior art are solved, and efficient and low-cost electrocatalytic hydrogen evolution effect is achieved, and good stability is maintained.
Patent Information
- Application Number
- CN202311512104.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-11-14
AI Technical Summary
In the prior art, the energy conversion efficiency of hydrogen evolution reaction (HER) in alkaline media is low, and precious metal-based catalysts such as platinum are limited in their commercial applications due to limited reserves and high costs.
Through structural engineering and interface engineering, a three-dimensional chrysanthemum-shaped CoMoO4@Ni3V/NF heterostructure electrocatalyst was synthesized by one-step hydrothermal method to optimize the morphology and interface structure of the catalyst, and improve its specific surface area and active site exposure.
It is achieved that exhibits low overpotential, fast Tafel slope, low charge transfer impedance and large electrochemically active surface area in 1.0M KOH, and remains strong stability after 1000 CV cycles.
Smart Images

Figure CN117626340B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanocomposite materials, and in particular, relates to a three-dimensional chrysanthemum-shaped CoMoO 4 @Ni 3 V / NF heterogeneous structure catalyst and its preparation method and application. Background Art
[0002] Hydrogen is an environmentally friendly renewable energy source and can serve as an ideal substitute for fossil energy to reduce excessive carbon dioxide emissions and environmental pollution. Although hydrogen production by water electrolysis has been industrialized for decades, the energy consumption in the electrolysis process is relatively high. The hydrogen evolution reaction (HER) in alkaline media has a high energy conversion efficiency. However, this reaction has a larger thermodynamic energy barrier, which greatly increases the production cost. At present, the most widely used are precious metal-based catalysts such as platinum (Pt), but limited reserves and high costs limit their commercial application. Therefore, there is an urgent need to develop low-cost and efficient electrocatalysts to replace precious metal-based catalysts.
[0003] Over the past few decades, transition metal catalysts CoMo, CoNi, NiMo, and other bimetallic nanoalloys have been favored in alkaline HER due to their abundant earth reserves, low price, and high conductivity. However, it is still necessary to further optimize their catalytic performance through strategies such as structural engineering and interface engineering. Summary of the invention
[0004] Structural engineering is used to adjust the morphology and nanostructure of the catalyst to increase the specific surface area of the catalyst, thereby exposing more active sites. Among them, nanoarrays with open skeletons can accelerate the penetration of electrolytes and the diffusion of bubbles, thereby ensuring the mass transfer process at high current density. The construction of heterostructures is an important part of interface engineering. Heterostructure materials have rich interfaces and optimized structures. Due to suitable electronic interactions, optimized band structures and more exposed active sites, the catalytic activity can be significantly improved.
[0005] The present invention provides a simple one-step hydrothermal method for synthesizing three-dimensional daisy-shaped CoMoO 4 @Ni 3 The V / NF heterogeneous structure electrocatalyst exhibits excellent performance by regulating structural engineering and interface engineering. The present invention uses transition metal vanadium (V) to improve the conductivity of nickel-based materials. In addition, the empty 3d orbital of V can attract the 3d electrons of Ni to form a Ni-OV bond, thereby increasing the binding strength between Ni and the reaction intermediate. In addition, the high valence state of V exhibits strong electrophilicity, which can promote the transformation of *OH to *OOH.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The object of the present invention is to provide a CoMoO 4 @Ni 3 V / NF nanocomposite material, which is composed of CoMoO 4 @Ni 3 V is loaded on NF, CoMoO 4 and Ni 3 A heterojunction structure is formed between the V, and the morphology is a three-dimensional daisy-shaped cluster. Multi-layer nanorod-like petals emanate from the central area, and Co, Mo, Ni, V and O elements are evenly distributed in the nanoclusters.
[0008] It is further defined that the diameter of the cluster is 6 μm to 8 μm. The diameter of the nanorod-shaped petals is 150 nm to 300 nm, the length is 1.5 μm to 2 μm, and the growth directions of the nanorods are different.
[0009] It is further defined that the molar ratio of the elements Co, Mo, Ni and V is 1:1:1:1.
[0010] The object of the present invention is to provide a CoMoO 4 @Ni 3 The preparation method of V / NF nanocomposite material is specifically carried out according to the following steps:
[0011] Step 1: Na 2 MoO 4 ·2H 2 O、Co(NO 3 ) 2 6H 2 O.Ni(NO 3 ) 2 6H 2 O、NH 4 VO 3 NH 4 F and urea were added into deionized water, stirred vigorously for at least 20 min, and ultrasonicated for at least 10 min to obtain a mixed solution;
[0012] Step 2: immerse the pretreated nickel foam in the mixed solution, perform hydrothermal crystallization, cool naturally to room temperature, and wash with anhydrous ethanol and deionized water in turn to obtain CoMoO 4 @Ni 3 V / NF nanocomposites.
[0013] It is further defined that in step 1, Na 2 MoO 4 ·2H 2 O、Co(NO 3 ) 2 6H2 O.Ni(NO 3 ) 2 6H 2 O、NH 4 VO 3 NH 4 F. The ratio of urea and deionized water is 1.3mmol:1.3mmol:1.3mmol:1.3mmol:0.8mmol:1mmol:30mL.
[0014] It is further defined that in step 1, the stirring rate is 750 rpm to 1500 rpm.
[0015] It is further defined that in step 1, the power of ultrasound is 40 Hz to 80 Hz.
[0016] It is further defined that in step 2, the nickel foam is pretreated by immersing it in 3M HCl, anhydrous ethanol and aqueous solution in sequence and ultrasonically treating them for 10 minutes each.
[0017] It is further defined that in step 2, the hydrothermal crystallization is carried out at 120° C. to 180° C. for at least 9 hours.
[0018] It is further defined that in step 2, the hydrothermal crystallization is carried out in a polytetrafluoroethylene-lined stainless steel autoclave.
[0019] The above CoMoO 4 @Ni 3 V / NF nanocomposite or CoMoO prepared by any of the above methods 4 @Ni 3 V / NF nanocomposites were used as electrocatalysts.
[0020] It is further defined that it is used as a working electrode for electrocatalytic hydrogen evolution.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] CoMoO of the present invention 4 @Ni 3 V / NF hydrogen evolution electrocatalyst in 1.0 M KOH, 10 mA cm -2 The current density showed a low overpotential of 48mV and a -1 The Tafel slope, charge transfer impedance of 3.25Ω and large electrochemically active surface area (ECSA, 18.64mF cm -2 ). After 1000 CV cycles, CoMoO 4 @Ni 3The LSV curve of V / NF has almost no change, showing strong stability. 4 @Ni 3 The V / NF electrocatalyst has an open structure and a short diffusion path. 4 with Ni 3 The synergistic effect between V can promote charge transfer, accelerate the diffusion of ions and water, and quickly release hydrogen and oxygen, improving the electrocatalytic performance.
[0023] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1(a) is CoMoO 4 @Ni 3 SEM image of V / NF electrocatalyst;
[0025] Figure 1(b) is CoMoO 4 @Ni 3 Scanning image of Co, Mo, Ni, V and O elements of V / NF electrocatalyst;
[0026] Figure 2 It's CoMoO 4 @Ni 3 XRD pattern of V / NF electrocatalyst;
[0027] Figure 3 It's CoMoO 4 @Ni 3 HRTEM images of V / NF at different magnifications;
[0028] Figure 4 It's CoMoO 4 @Ni 3 XPS patterns of Co 2p (a), Mo 3d (b), Ni 2p (c), O1s (d), and V 2p (e) of V / NF and CoMoNi / NF electrocatalysts.
[0029] Figure 5 It's CoMoO 4 @Ni 3 Comparison of the activities of V / NF and CoMoNi / NF electrocatalysts in alkaline environment: (a) polarization curve; (b) Tafel slope of the corresponding electrode material; (c) electrochemical impedance spectroscopy; (d) double layer capacitance diagram (Cdl); (e) CoMoO 4 @Ni 3Comparison of polarization curves before and after 1000 V / NF cyclic voltammetry (CV) tests. DETAILED DESCRIPTION
[0030] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0031] Example 1: In this example, three-dimensional chrysanthemum-shaped CoMoO 4 @Ni 3 The V / NF heterostructure catalyst was synthesized by a one-step hydrothermal method; the specific synthesis process was achieved by the following steps:
[0032] Step 1, 1.3 mmol Na 2 MoO 4 ·2H 2 O, 1.3mmolCo(NO 3 ) 2 6H 2 O, 1.3mmol Ni(NO 3 ) 2 6H 2 O, 1.3 mmol NH 4 VO 3 , 0.8mmol NH 4 F and 1 mmol urea were mixed in 30 mL deionized water, stirred vigorously at 900 rpm for 20 min, and ultrasonicated at 60 kHz for 10 min to obtain a mixed solution;
[0033] Step 2: The mixed solution obtained in step 1 was transferred to a 35 mL polytetrafluoroethylene-lined stainless steel autoclave, and the pretreated nickel foam NF (length 4 cm × width 1 cm × thickness 0.3 mm) was immersed in the mixed solution and hydrothermally crystallized at 150 ° C for 9 h. After naturally cooling to room temperature, it was rinsed with anhydrous ethanol for 3 times and then rinsed with deionized water for 3 times to obtain CoMoO 4 @Ni 3 V / NF catalyst.
[0034] In this embodiment, the nickel foam is pretreated by immersing it in 3M HCl, anhydrous ethanol and aqueous solution in sequence and ultrasonically treating them for 10 min each.
[0035] Comparative Example: The synthesis of CoMoNi / NF is achieved by the following steps:
[0036] 1.3mmol Na2 MoO 4 ·2H 2 O, 1.3mmol Co(NO 3 ) 2 6H 2 O, 1.3mmol Ni(NO 3 ) 2 6H 2 O, 0.8 mmol NH 4 F and 1 mmol urea were mixed in 30 mL deionized water, stirred vigorously at 900 rpm for 20 min, and ultrasonicated at 60 kHz for 10 min to obtain a mixed solution;
[0037] The mixed solution was transferred to a 35 mL polytetrafluoroethylene-lined stainless steel autoclave. The treated NF (4 cm long × 1 cm wide × 0.3 mm thick) was then immersed in the polytetrafluoroethylene autoclave lining and crystallized at 150 °C for 9 h. After naturally cooling to room temperature, it was first rinsed with anhydrous ethanol for 3 times and then rinsed with deionized water for 3 times to obtain CoMoNi / NF.
[0038] CoMoO prepared by the method of Example 1 4 @Ni 3 The SEM image of the V / NF electrocatalyst is shown in Figure 1(a); CoMoO 4 @Ni 3 The surface scan of Co, Mo, Ni, V and O elements of V / NF electrocatalyst is shown in Figure 1(b).
[0039] from Figure 1a It can be seen that CoMoO 4 @Ni 3 V / NF exhibits a three-dimensional daisy-like cluster with a diameter of about 6μm-8μm, and multiple layers of nanorod-like petals emanating from the central region, with a diameter of 150nm-300nm and a length of 1.5μm-2μm. Figure 1b The elemental surface scan shows that Co, Mo, Ni, V and O are evenly distributed in the nanoclusters, and it is clearly observed that Co, Mo and O are combined in the nanoparticles, and Ni is combined with V. 4 @Ni 3 The V / NF electrocatalyst was successfully synthesized.
[0040] The CoMoO prepared by the method of Example 1 was characterized by XRD. 4 @Ni 3 The crystal phase of V was characterized, and the XRD pattern is shown in Figure 2 As shown. Figure 2It can be seen that the three strong diffractions at 2θ of 44.5, 51.9 and 76.4° correspond to the (111), (220) and (311) crystal planes of metal Ni (PDF#04-0850). The diffraction peaks at 2θ of 25.5, 32.0, 38.8, 40.2, 41.6, 48.7, 54.5, 60.4 and 64.5° can be well attributed to CoMoO 4 The (201), (131), (040), (003), (222), (133), (440), (424) and (243) planes (PDF#21-0868). The diffraction patterns at 2θ of 24.6, 28.0, 35.8, 44.0, 51.6, 59.7, 70.4 and 75.1 should be attributed to Ni 3 V's (002), (102), (101), (110), (112), (200), (211), (105), and (204) planes (PDF#13-0523). 4 and Ni 3 V two phases exist at the same time.
[0041] CoMoO prepared by the method of Example 1 4 @Ni 3 The results of HRTEM of V / NF are as follows Figure 3 As shown by Figure 3 It can be seen that the intercrystalline spacing d = 0.143nm corresponds to CoMoO 4 The (201) crystal plane, the intercrystalline spacing d = 0.243nm corresponds to Ni 3 The (112) crystal plane of V is consistent with the XRD results, indicating that CoMoO 4 with Ni 3 V forms a heterostructure and forms rich interfaces.
[0042] CoMoO prepared by the method of Example 1 4 @Ni 3 Co2p XPS patterns of CoMoNi / NF electrocatalysts prepared by V / NF and comparative method are shown in Figure 4 As shown in a, Figure 4 a It can be seen that the two main peaks at binding energies of 780.5 and 796.4 eV correspond to Co2p 3 / 2 and Co 2p 1 / 2 , the peaks at 780.1 and 796.5 eV correspond to Co 3+ , the peaks at 782.7 and 797.8 eV correspond to Co 2 + . Description CoMoO 4 @Ni 3V / NF and CoMoNi / NF electrocatalysts with the presence of Co 3+ and Co 2+ .
[0043] CoMoO prepared by the method of Example 1 4 @Ni 3 Mo3d XPS patterns of CoMoNi / NF electrocatalysts prepared by V / NF and comparative method are shown in Figure 4 As shown in b. Figure 4 b It can be seen that the peaks at binding energies of 233.3 and 236.3 eV correspond to Mo 4+ , the two peaks at 232.4 and 235.4 eV correspond to Mo 5+ (split width is 3 eV), which is consistent with the reported Mo 5+ The peak of CoMoO 4 @Ni 3 V / NF compared with CoMoNi, Mo 4+ The peak area of the ions decreases, indicating that Mo ions move to a higher valence state. 4 Successfully synthesized.
[0044] CoMoO prepared by the method of Example 1 4 @Ni 3 XPS images of Ni2p of CoMoNi / NF electrocatalyst prepared by V / NF and comparative method are shown in Figure 4 As shown in c, Figure 4 c shows that two satellite peaks are observed at binding energies of 862.8 and 881.0 eV, and the peaks at 856.8 and 874.8 eV are attributed to Ni 3+ The presence of satellite peaks confirms the existence of different valence states of Ni species. It is worth noting that CoMoO 4 @Ni 3 Co in V / NF catalyst 2+ 、Mo 4+ and Ni 3+ The binding energies of CoMoO 4 and Ni 3 The interaction between V changes the coordination environment and charge transfer effect of the active site.
[0045] In CoMoO 4 @Ni 3 V (0.15) / NF O1s spectrum (such as Figure 4 d), the three peaks with binding energies located at 530.42 eV, 531.29 eV and 532.07 eV can be attributed to metal-OH, metal-O-metal species and adsorbed surface water, respectively. Figure 4e is the XPS pattern of V 2p, the peaks at 516.4 and 522.9 eV are attributed to V 3+ , the peaks at 518.8 and 525.8 eV are attributed to V 4+ , the peaks at 517.4 and 524.6 eV are attributed to V 5+ , indicating that V species have a variety of different valence states.
[0046] The HER activity of the catalyst was evaluated in 1 M KOH solution using a standard three-electrode system. The working electrodes were CoMoNi / NF and CoMoO 4 @Ni 3 V / NF (prepared electrocatalyst, geometric area 1×1 cm -2 ), reference electrode (saturated calomel electrode) and counter electrode (graphite electrode). Figure 5 The LSV test results of a show that CoMoO 4 @Ni 3 V / NF at 10 mA cm -2 The overpotential at this current density is only 48 mV, which is significantly lower than the overpotential of CoMoNi / NF (252 mV@10 mA cm -2 ). Description CoMoO 4 @Ni 3 The V / NF catalyst has excellent HER activity. The Tafel slope of the catalyst was calculated based on the LSV curve, and the catalytic reaction kinetics were compared. Figure 5 The fitting results of b show that CoMoO 4 @Ni 3 The Tafel slopes of V / NF and CoMoNi / NF are 82.1 mV dec, respectively. -1 、118.4mV dec -1 , indicating that CoMoO 4 @Ni 3 V / NF catalysts have faster reaction kinetics. Electrochemical impedance spectroscopy (EIS) can reflect the system impedance (Rs, usually solution impedance) of the electrocatalytic reaction and the charge transfer impedance (Rct) present at the cathode electrode / electrolyte interface. The smaller the radius of the semicircle, the better the charge transfer kinetics. Figure 5 c analysis shows that CoMoO 4 @Ni 3 The charge transfer resistance (Rct) of V / NF and CoMoNi / NF are 3.25Ω and 10.25Ω, respectively, indicating that CoMoO 4 @Ni 3 The charge transfer rate of V / NF in the electrolyte is faster. Figure 5 d is the double-layer capacitance diagram of the catalyst at the solid / liquid interface. It can be seen from the figure that CoMoO4 @Ni 3 The V / NF capacitance is 18.64mF cm -2 , which is higher than the capacitance of CoMoNi / NF (8.75mF cm -2 ), indicating that its unique three-dimensional chrysanthemum-like morphology has a larger surface area, which adds more active sites for the electrocatalytic hydrogen evolution process. In addition, the stability and life of the catalyst are two important indicators for evaluating the performance of the material, which can be characterized by continuous cyclic voltammetry testing. Figure 5 As shown in e, after 1000 CV cycles, the CoMoO 4 @Ni 3 From the polarization curves before and after the V / NF test, it can be seen that the curves are basically unchanged, indicating that the catalyst has good stability.
Claims
1. CoMoO4@Ni3V / NF nanocomposite material, characterized in that: The nanocomposite material is composed of CoMoO4@Ni3V loaded on NF, and a heterojunction structure is formed between CoMoO4 and Ni3V. The morphology is a three-dimensional daisy-shaped cluster, and multiple layers of nanorod-shaped petals are emitted from the central area. Co, Mo, Ni, V and O elements are evenly distributed in the nanoclusters.
2. The nanocomposite material according to claim 1, characterized in that: The diameter of the cluster is 6 μm to 8 μm, and the diameter of the nanorod-shaped petals is 150 nm to 300 nm and the length is 1.5 μm to 2 μm.
3. The nanocomposite material according to claim 1 or 2, characterized in that: The molar ratio of the elements Co, Mo, Ni and V is 1:1:1:
1.
4. The method for preparing the nanocomposite material according to any one of claims 1 to 3, characterized in that: The preparation method is carried out according to the following steps: Step 1, adding Na2MoO4·2H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, NH4VO3, NH4F and urea into deionized water, stirring vigorously for at least 20 min, and ultrasonicating for at least 10 min to obtain a mixed solution; Step 2: Immerse the pretreated nickel foam in the mixed solution, perform hydrothermal crystallization, cool naturally to room temperature, and wash with anhydrous ethanol and deionized water in sequence to obtain a CoMoO4@Ni3V / NF nanocomposite material.
5. The preparation method according to claim 4, characterized in that: In step 1, the ratio of Na2MoO4·2H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, NH4VO3, NH4F, urea and deionized water is 1.3mmol:1.3mmol:1.3mmol:1.3mmol:0.8mmol:1mmol:30mL.
6. The preparation method according to claim 4, characterized in that: In step 1, the stirring rate is 750 rpm to 1500 rpm.
7. The preparation method according to claim 4, characterized in that: In step 1, the power of ultrasound is 40 Hz to 80 Hz.
8. The preparation method according to claim 4, characterized in that: In step 2, the nickel foam is pretreated by immersing it in 3M HCl, anhydrous ethanol and aqueous solution in sequence and ultrasonically treating it for 10 minutes each; and hydrothermally crystallizing it at 120° C. to 180° C. for at least 9 hours.
9. The nanocomposite material according to any one of claims 1 to 3 or the nanocomposite material prepared by the method according to any one of claims 4 to 8 is used as an electrocatalyst.
10. The use according to claim 9, characterized in that: It is used as a working electrode for electrocatalytic hydrogen evolution.
Citation Information
Patent Citations
KR20240126523A